PENGARUH BID-ASK SPREAD, MARKET VALUE DAN VARIANCE RETURN TERHADAP HOLDING PERIOD SAHAM - Aris Susetyo; Farida Niati (Fakultas Ekonomi Universitas Pekalongan, 2019)
The purpose of this research is to determine the influence of bid-ask spread, market value and variance return to holding period partially as well as simultaneous on the LQ45 index stocks 2016. The data which are being used for this research is secondary data as daily data obtained in www.idx.co.id. The population in this research is LQ45 Index companies listed in Indonesia Stock Exchange 2016. Sampling techniques is purposive sampling method that generates numbers of samples as much as 39 companies and 246 days forming a panel data as much as 9594 samples. Analytical techniques is panel data regression model: Fixed Effect Model with application software Eviews 10. Hypothesis test the results showed that: 1) bid-ask spread has positive influence and significantly to the holding period, 2) market value has negative influence and significantly to holding period, 3) variance return has negative influence and significantly to the holding period, 4) bid-ask spread, market value and variance return simultaneously have influence on the holding period. Holding period can be explained by the influence of variations independent variable: bid-ask spread, market value and variance return as 97.62%, while 2.38% influenced by other variables out of the research model.Keywords: holding period, bid-ask spread, market value, variance return